Oncologic outcomes of salvage surgery and immune checkpoint inhibitor therapy in recurrent head and neck squamous cell carcinoma: A single‐institution retrospective study. Issue 11 (5th August 2022) - Konuthula, Neeraja; Do, Olivia A.; Gobillot, Ted; Rodriguez, Cristina P.; Futran, Neal D.; Houlton, Jeffrey; Barber, Brittany R.
Abstract: Background: Survival outcomes in recurrent head and neck squamous cell carcinoma (HNSCC) are poor. This study aimed to compare survival outcomes between salvage surgery and immunotherapy in patients with recurrent advanced HNSCC. Methods: Patients with advanced stage (stage III or IV) recurrent HNSCC following treatment with platinum‐based chemotherapy were included. Survival was estimated using the Kaplan–Meier method, and Cox regression was used for multivariate logistic regression. Results: Two‐year overall survival after salvage surgery was 68.6% and after immunotherapy patients was 24.6%. Multivariate logistic regression showed that salvage surgery was associated with improved survival without statistical significance (hazard ratio [HR] 0.12, p = 0.25). Subgroup analysis of patients with oral cavity/oropharyngeal cancer noted improved survival with salvage surgery over immunotherapy (HR 0.006, p = 0.01) and decreased survival with neutrophil‐to‐lymphocyte ratio (NLR) > 5 (HR 6.4, p = 0.02). Conclusion: Our retrospective single‐institutional data suggest that resectable advanced stage recurrent HNSCC may have improved survival with salvage surgery in appropriately selected patients, but larger prospective studies are required.